The Effect of AcceleDentÂ® Device on Both Gingival Health Condition and Levels of Salivary Interleukin-1-Î²eta and Tumor Necrosis Factors-Alpha in Patients under Fixed Orthodontic Treatment - Ahmed, Zaid S; Ahmed, Noor S; Ghaib, Nidhal H (Journal of Baghdad College of Dentistry, 2015)
Background: Orthodontic tooth movement is characterized by tissue reactions, which consist of an inflammatory response in periodontal ligament and followed by bone remodeling in the periodontium depending on the forces applied. These processes trigger the secretion of various proteins and enzymes into the saliva.The purpose of this study was to evaluate the activity of alkaline phosphatase (ALP) in saliva during orthodontic tooth movement using different magnitude of continuous orthodontic forces. Materials and Methods: Thirty orthodontic patients (12 males and 18 females) aged 17-23 years with class II division I malocclusion all requiring bilateral maxillary first premolar extractions were randomly divided into three groups according to the magnitude of the force application (40, 60 and 80gm). A sectional fixed appliance was bonded and designed to give labial force to the maxillary first premolar for three weeks. Unstimulated saliva was collected from the patients before force application, then 1 hour after force application, followed by 1 day, 7 days, 14 days and 21 days.Salivary levels of ALP were measured using spectrophotometer and compared with the baseline level. Results: The results revealed that ALP enzymelevel increased with increasing magnitude of orthodontic force (from 40 to 80gm). This was statistically insignificant after 1 hour and 1 day of force application, but significant after 7, 14 and 21 days.The ALP level significantly increased from baseline after 7 days of force application and peaked at 21 days for all the three force levels. Conclusions: The ALP level reflect the biological activity that takes place in the periodontium during orthodontic tooth movement, and therefore they can be used as a diagnostic tool for monitoring of correct orthodontic tooth movement in clinical practice.